2016
DOI: 10.1093/jee/tow097
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of the Invasive SpeciesMetcalfa pruinosa(Hemiptera: Flatidae) in the Republic of Korea

Abstract: Metcalfa pruinosa (Say, 1830) (Hemiptera: Flatidae) has caused substantial agricultural damage since its recent introduction to the Republic of Korea; however, the source of this introduction is still unclear. To examine the genetic divergence and phylogenetic relationships among several populations of M. pruinosa from Korea and foreign countries, 251 COI sequences from 251 samples collected from Korea, France, Italy, Spain, Slovenia, and the United States were newly analyzed, together with seven published COI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…A mitotype already reported in GenBank/EMBL by four different entries (Hap6; corresponding to haplotypes H1 or H2 of Park et al . 32 ) was the most frequent in all our honeys (from about 84% to 90% of reads). Another mitotype (not yet described by previous studies, according to publicly available sequences) was identified only in the Corsican honey that accounted 8.5% of total M .…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…A mitotype already reported in GenBank/EMBL by four different entries (Hap6; corresponding to haplotypes H1 or H2 of Park et al . 32 ) was the most frequent in all our honeys (from about 84% to 90% of reads). Another mitotype (not yet described by previous studies, according to publicly available sequences) was identified only in the Corsican honey that accounted 8.5% of total M .…”
Section: Resultsmentioning
confidence: 84%
“…Reads matching the most frequent database mitotype (Hap1, reported in 119 entries and corresponding to H3, H8, H9, H15, H16, H18 or H19 of Park et al . 32 ) were obtained in all honeys, except in the silver fir honeydew honey produced in Emilia Romagna. However, this mitochondrial haplotype (Hap1; Table 3 and Figure 2 ) was not the most frequent in all our samples (ranging from 6% to 15% of total M .…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations